1966
DOI: 10.1088/0029-5515/6/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a hot-cathode discharge in a magnetic field at low pressures

Abstract: The authors present results of the investigation of an incandescent-cathode discharge in an equipotential volume in a magnetic field of 2000 Oe. In the pressure range studied, 2 × 10−6 to 10−4 Torr, there is formed a plasma column negatively charged in relation to the surrounding walls. It is established that, when the pressure of the neutral gas is increased, such a discharge becomes unstable. A plasma torch is formed which rotates steadily in the direction of the electrons and escapes from the region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 2 publications
3
19
0
Order By: Relevance
“…The nature of the fluctuations has remained unexplained reliably for several decades. Low frequency oscillations were also observed in many other experiments (see, for example, [7][8][9]).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The nature of the fluctuations has remained unexplained reliably for several decades. Low frequency oscillations were also observed in many other experiments (see, for example, [7][8][9]).…”
Section: Introductionsupporting
confidence: 69%
“…In this paper, we investigate the possibility of explaining the nature of low-frequency oscillations observed in experiments by the instability of the relative motion along the azimuth of electrons and ions of nonneutral plasma. Using the results of papers [1,2,10,11], the characteristics of the expected electron-ion instability are estimated for the values of parameters typical for experiments [4][5][6][7][8][9]. The frequencies and growth rates of oscillations are estimated depending on the intensities of the radial electric and longitudinal magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…[88,87,77] and Ref. [89,77], respectively. Then, we calculate P7 Li→ 7 Li and found that P7 Li→ 7 Li is also close to 1 for the cases we are interested in.…”
Section: E Dissociation Of Non-thermally Produced LImentioning
confidence: 99%
“…However, long-wavelength low-frequency oscillations with an azimuthal number m = 1 are still observed in experiments with non-neutral plasma (see, for example, [8][9][10][11][12][13]). Apparently, there is instability of long-wavelength along the magnetic field lowfrequency oscillations in a negative radial electric field (directed to the axis) with a significant degree of neutralization and partial filling of the waveguide with plasma:…”
Section: Introductionmentioning
confidence: 99%
“…Can the relative motion of electrons and ions of nonneutral plasma be the cause of the low-frequency instabilities observed in the above-mentioned [8][9][10][11][12][13] and other similar experiments? For this, in any case, it is necessary that the eigenmodes of oscillations with the azimuthal number m = 1 fall into the region of low (ionic) frequencies at the values of the plasma parameters (4).…”
Section: Introductionmentioning
confidence: 99%